2022
DOI: 10.1017/langcog.2022.36
|View full text |Cite
|
Sign up to set email alerts
|

Vocal iconicity in nominal classification

Abstract: While recent years have seen a substantial increase of studies investigating vocal iconicity in the lexicon of spoken languages, its presence in grammatical structures is poorly understood. This study investigates the presence of vocal iconicity in nominal classification systems by collecting nominal classification devices from the two main system types: 210 non-agreeing languages (126 families) and 151 agreeing languages (123 families). To detect overrepresentations of sound types in class meanings, the nomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(65 reference statements)
1
0
0
Order By: Relevance
“…Since /m/ was the type of sound that was generated during breastfeeding, an association was formed between breast and /m/ [ 26 , 74 ] Alternatively, /m/ have been found to be associated with cuteness in Japanese [ 72 , 73 ] The consonant /m/ is widely observed in brand names related to baby diapers [ 72 ]. This finding also resonates with a study by Erben Johansson & Cronhamn [ 75 ] who found that nasals occur more frequently in feminine nouns. Considering the rich imagery invoked by the consonant /m/, the association between the consonant /m/ to femininity may be due to a combination of these imagery or concepts invoked.…”
Section: Discussionsupporting
confidence: 91%
“…Since /m/ was the type of sound that was generated during breastfeeding, an association was formed between breast and /m/ [ 26 , 74 ] Alternatively, /m/ have been found to be associated with cuteness in Japanese [ 72 , 73 ] The consonant /m/ is widely observed in brand names related to baby diapers [ 72 ]. This finding also resonates with a study by Erben Johansson & Cronhamn [ 75 ] who found that nasals occur more frequently in feminine nouns. Considering the rich imagery invoked by the consonant /m/, the association between the consonant /m/ to femininity may be due to a combination of these imagery or concepts invoked.…”
Section: Discussionsupporting
confidence: 91%